Eesti perekondliku hüperkolesteroleemia käsitlusjuhend - Viigimaa, Margus; Blöndal, Mai; Hedman, Anu; Härma-Jõks, Piret; Irs, Alar; Pajusalu, Sander; Raidmäe, Maila; Serg, Martin (Eesti Arst, 2023)
Eesti Arst 2023; 102(4):237–240